2022
DOI: 10.1055/a-1730-5091
|View full text |Cite
|
Sign up to set email alerts
|

Silencing LncRNA PVT1 Reverses High Glucose-Induced Regulation of the High Expression of PVT1 in HRMECs by Targeting miR-128-3p

Abstract: This paper aims to discuss the possibility of lncRNA PVT1 as a diagnostic biomarker for diabetic retinopathy (DR) and explore the underlying mechanism. Real-time quantitative polymerase chain reaction (RT-qPCR) was selected to determine the expression level of lncRNA PVT1 in the serum of all subjects. The receiver operating characteristic (ROC) curve reflected the diagnostic significance of PVT1 for DR patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The miR-1228-3p mimic or inhibitor and the vectors (WT-ASMTL-AS1 or MUT-ASMTL-AS1) were co-transfected into SK-OV-3 and UACC-1598 cells. Luciferase activity was detected using Dual-Luciferase Reporter Assay System kit (Promega, USA) [20].…”
Section: Dual-luciferase Reporter Assaymentioning
confidence: 99%
“…The miR-1228-3p mimic or inhibitor and the vectors (WT-ASMTL-AS1 or MUT-ASMTL-AS1) were co-transfected into SK-OV-3 and UACC-1598 cells. Luciferase activity was detected using Dual-Luciferase Reporter Assay System kit (Promega, USA) [20].…”
Section: Dual-luciferase Reporter Assaymentioning
confidence: 99%
“…Particularly, in diabetic patients with DR or in human retinal endothelial cells cultured with HG concentrations, the upregulation of several different lncRNAs has been recently reported. Although further analyses are needed, for most of the mentioned lncRNAs, preliminary evidence suggests a putative role in DR. Of note, the in vitro knockdown of these lncRNAs ameliorates retinal dysfunctions improving various related-biological processes, such as proliferation, apoptosis, migration, angiogenesis, inflammation, or redox state [ 62 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. For instance, ARPE-19 cells exposed to HG display increased expression of IGF2 Antisense RNA ( IGF2-AS ) and enhanced apoptosis, and IGF2-AS silencing restrains apoptosis, inducing IGF2/Akt signaling and reducing Casp-9 expression [ 114 ].…”
Section: Long Non Coding Rnas With Increased Expression In Diabetic R...mentioning
confidence: 99%
“…Additionally, a recent work reports that the knockdown of TUG1 ameliorates diabetic retinal vascular dysfunction through regulating miR-524-5p/ FGFR2 axis [ 124 ]. Furthermore, independent studies in patients with DR showed the negative correlations between Plasmacytoma Variant translocation 1 ( PVT1 ) and miR-128-3p, as well as between the lncRNA OGRU and miR-320, supporting that also these lncRNAs may affect miRNA-mediated networks [ 62 , 125 ]. Particularly, in Müller cells cultured in HG conditions, OGRU suppression significantly restores miR-320 expression, and it represses the ubiquitin-specific peptidase 14 ( USP14 ) expression whereas, on the opposite, the upregulation of miR-320 reduces TGF-β1 signaling and impairs inflammation and oxidative stress [ 126 ].…”
Section: Long Non Coding Rnas With Increased Expression In Diabetic R...mentioning
confidence: 99%
“…Additionally, starBase predicted the presence of a putative complementary sequence for miR-29a-3p on lncRNA plasmacytoma variant translocation 1 (PVT1). LncRNA PVT1 is highly expressed and acts as an oncogene in multiple cancers [ 23 ], and also functions in ophthalmic diseases such as diabetic retinopathy [ 24 ], retinoblastoma [ 25 ], and diabetic cataract [ 26 ]. However, the mechanism underlying the role of lncRNA PVT1 in glaucoma remains unknown.…”
Section: Introductionmentioning
confidence: 99%